Above the Reich : deadly dogfights, blistering bombing raids, and other war stories from the greatest American air heroes of World War II, in their own words - Heaton, Colin D.; Lewis, Anne-Marie (Dutton Caliber, 2021)
"Sensational eyewitness accounts from the most heroic and legendary American aviators of World War II, never before published as a book"--